2018
DOI: 10.5194/adgeo-45-13-2018
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic short term wind power forecasts using deep neural networks with discrete target classes

Abstract: Abstract. Usually, neural networks trained on historical feed-in time series of wind turbines deterministically predict power output over the next hours to days. Here, the training goal is to minimise a scalar cost function, often the root mean square error (RMSE) between network output and target values. Yet similar to the analog ensemble (AnEn) method, the training algorithm can also be adapted to analyse the uncertainty of the power output from the spread of possible targets found in the historical data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…To analyze the results, the mean absolute percentage error (MAPE), normalized mean absolute error (NMAE) and normalized root mean square error (NRMSE) metrics are used, calculated as the mean value in the forecasting horizons (24 h and 6 h). As in [34], models have been developed for different forecasting horizons [26,27,33]. However, an extensive analysis of the literature conducted by the authors of the present study has found that the models developed to date only consider a specific and fixed number of prior 1-h periods (periods prior to the prediction hour).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…To analyze the results, the mean absolute percentage error (MAPE), normalized mean absolute error (NMAE) and normalized root mean square error (NRMSE) metrics are used, calculated as the mean value in the forecasting horizons (24 h and 6 h). As in [34], models have been developed for different forecasting horizons [26,27,33]. However, an extensive analysis of the literature conducted by the authors of the present study has found that the models developed to date only consider a specific and fixed number of prior 1-h periods (periods prior to the prediction hour).…”
Section: Introductionmentioning
confidence: 94%
“…In most cases, good performances for specific forecasting horizons have been obtained. The techniques that have been used range from simple heuristics [14][15][16][17][18][19][20] to systems which employ artificial intelligence [21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques range from simple heuristics [13] - [17] to artificial intelligence [18] - [29]. This paper focuses on models which employ the technique of artificial neural networks (ANNs) to forecast wind power production [21], [22], [24]- [26], [28], [29].…”
Section: Introductionmentioning
confidence: 99%
“…To analyse the results, the mean absolute percentage error (MAPE), normalized mean absolute error (NMAE) and normalized root mean square error (NRMSE) metrics are used, calculated as the mean value in the forecasting horizons (24 hours and 6 hours). As in [29], models have been developed for different forecasting horizons [21], [22], [28]. However, an extensive analysis of the literature has found that the models developed to date only consider a specific and fixed number of prior 1-h periods (periods prior to the forecasting hour).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many papers related to power prediction for wind turbines have been published, like [14], where researchers created a turbine regression tree model to predict power output. In [15], authors used deep neural networks with discrete target classes to do probabilistic short-term wind power forecasts. Besides, BP and RBF neural networks were applied to realize wind power short-term prediction in [16].…”
Section: Introductionmentioning
confidence: 99%